2009
DOI: 10.1517/14656560903215871
|View full text |Cite
|
Sign up to set email alerts
|

Propionyll-carnitine: intermittent claudication and peripheral arterial disease

Abstract: Peripheral arterial disease (PAD) is a clinical manifestation of underlying aorto-iliac and leg atherosclerosis that is characterized by different stages of stenosis and obstruction. It affects approximately 12% of the adult population and about 20% of people over the age of 70 years, and is associated with increased cardiovascular (CV) and cerebrovascular morbidity. Intermittent claudication (IC) is the major symptom of PAD; it is defined as cramping leg pain (in the buttock, thigh, or calf) while/after clim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 64 publications
0
14
0
2
Order By: Relevance
“…Propionylcarnitine have effects on endothelial cells and may thereby influence the trafficking of immunocompetent cells (Andreozzi 2009; Malaguarnera 2012). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Propionylcarnitine have effects on endothelial cells and may thereby influence the trafficking of immunocompetent cells (Andreozzi 2009; Malaguarnera 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Oral propyonyl-L-carnitine has been tried in the treatment of human diseases (Andreozzi 2009; Malaguarnera 2012), mainly cardiovascular disease, but it has also shown beneficial effects in a randomized, double-blind, placebo-controlled study of patients with ulcerative colitis, i.e. an autoimmune disease (Mikhailova et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The clinical effect of L -carnitine treatment has been documented in patients with peripheral vascular disease. It has been shown to correct secondary muscle L -carnitine deficiency in patients with peripheral vascular disease, significantly improving walking capacity [25]. There have been several studies evaluating L -carnitine treatment in cardiovascular diseases and heart failure [26].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the effects of ALC on PAD have been poorly evaluated. Some reviews focused on these effects are the main sources considered in the present analysis 26,27,29…”
Section: Therapeutic Effects Of L-carnitine Analogs On Cardiovascularmentioning
confidence: 99%
“…Wiseman and Brogden concluded that PLC had no direct vasoactive effects in patients with IC 29. However, other scholars mentioned the capacity of PLC to improve endothelial function,26,42 and some years later, Andreozzi gathered clinical evidence demonstrating the beneficial effects of PLC treatment on the vasculature of patients with PAD 27. More precisely, this recent review concluded that PLC has an ability to enhance flow mediated dilatation (FMD) in the brachial artery,43 even when impaired post-exercise 44.…”
Section: Therapeutic Effects Of L-carnitine Analogs On Cardiovascularmentioning
confidence: 99%